Hydrogen Peroxide Production by the Spot-Like Mode Action of Bisphenol A - Adamakis, Ioannis-Dimosthenis S.; Sperdouli, Ilektra; Eleftheriou, Eleftherios P.; Moustakas, Michael (Frontiers in Plant Science, 2020)
Bisphenol A (BPA), an intermediate chemical used for synthesizing polycarbonate plastics, has now become a wide spread organic pollutant. It percolates from a variety of sources, and plants are among the first organisms to encounter, absorb and metabolize it, while its toxic effects are not yet fully known. Therefore, we experimentally studied the effects of aqueous BPA solutions (50 and 100 mg L-1, for 6, 12 and 24 hours) on photosystem II (PSII) functionality and evaluated the role of reactive oxygen species (ROS) on detached leaves of the model plant Arabidopsis thaliana. Chlorophyll fluorescence imaging analysis revealed a spatiotemporal heterogeneity in the quantum yields of light energy partitioning at PSII in Arabidopsis leaves exposed to BPA. Under low light PSII function was negatively influenced only at the spot-affected BPA zone in a dose- and time-depended manner, while at the whole leaf only the maximum photochemical efficiency (Fv/Fm) was negatively affected. However, under high light all PSII photosynthetic parameters measured were negatively affected by BPA application, in a time-depended manner. The affected leaf areas by the spot-like mode of BPA action showed reduced chlorophyll autofluorescence and increased accumulation of hydrogen peroxide (H2O2). When H2O2 was scavenged via N-acetylcysteine under BPA exposure, PSII functionality was suspended, while H2O2 scavenging under non-stress had more detrimental effects on PSII function than BPA alone. It can be concluded that the necrotic death-like spots under BPA exposure could be due to ROS accumulation, but also H2O2 generation seems to play a role in the leaf response against BPA-related stress conditions.